Homelessness, crack use, and length of stay as predictors of planned discharge from night care in a Psychosocial Care Center - Gabriella de Andrade Boska; Rogério da Silva Ferreira; Heloisa Garcia Claro; Priscilla Oliveira Luz; Márcia Aparecida Ferreira de Oliveira (Hospital de Clínicas de Itajubá, 2021)
Objective: identify predictors of planned discharge to night care embracement in a Psychosocial Care Center Alcohol and Drugs (CAPS AD III). Methods: Quantitative, retrospective, and documentary study of 560 medical records of people with problems resulting from the use of alcohol and other drugs who were admitted to the hospital at night in a CAPS AD III in São Paulo, over five years. As a dependent variable, the type of discharge was used (planned or not). As independent variables, the profile of the subjects related to substance use and time in hospital. Results: 1,097 admissions were identified with 50.4% of unplanned discharge associated with homelessness (p = 0.007), problematic use crack (p = 0.015), length of reception proposed by the team (p = 0.029) and length of stay of the user (p < 0.001). Conclusion: Being homeless, problematic use of crack, and lack of user participation on the decisions regarding length of stay in CAPS AD III were associated with unplanned discharge.